Behavioral operational research : theory, methodology and practice - Kunc, Martin; Malpass, Jonathan; White, Leroy (Palgrave Macmillan, 2016)
Behavioral research is making a significant impact on many academic disciplines. Its status as the source of some of the most profound research in the social sciences is unparalleled. Therefore, it is not surprising that interest in Behavior and Operational Research (OR) is burgeoning, even though understanding the relationship between knowledge, behavior and action has been an academic preoccupation in OR since the beginning of the discipline. This book introduces the idea of Behavioral OR, where the theoretical and empirical developments in the behavioral field are making an impression on OR academics and practitioners alike. The book provides a much needed overview that connects together theory, methodology and practice and offers the?state of the art? on Behavioral Operational Research theory and practice. The book not only includes chapters by leading academics, but also includes rich and insightful real-life case studies by practitioners.- Resumé vydavatel
Keywords: operační výzkum; rozhodování; logistika (management); lidské chování; operations research; decision making; business logistics; human behavior; elektronické knihy; sborníky; electronic books; papers of several authors